Pengaruh Gamifikasi terhadap Program Loyalitas pada Platform Tokopedia Indonesia - Thomas Hardianto; Arta Moro Sundjaja; Yuli Yuli; Giovanka Savina (Prosiding SISFOTEK, 2019)
The research objective is to develop a conceptual model for evaluating the determinant factors of loyalty program in Tokopedia. The data collection method is literature search. The authors search the literature in Google Scholar using relevant keywords. The authors use e-commerce development in Indonesia, government role in e-commerce development, user behavior, Indonesia e-commerce statistic, gamification, loyalty program as keywords. The authors found and used 45 articles that related with the antecedent of Tokopedia loyalty program. The antecedent of tokopedia loyalty program are gamified loyalty program, reward attractiveness, affective commitment. The mediating variable are playfulness, and attitude toward LP. The dependent variable is loyalty program.